Optimal Design and Distribution of Viscous Dampers for Shear Building Structures Under Seismic Excitations - Cetin, Huseyin; Aydin, Ersin; Ozturk, Baki (Frontiers in Built Environment, 2019)
Viscous dampers (VDs) are effective and widely used passive devices for the protection of civil structures, provided that appropriate design is carried out. For this purpose, an optimal design and optimum distribution of VDs method is presented for a shear building under the critical excitation by using random vibration theory in frequency domain. In the optimization, by using Differential Evolution (DE) algorithm, the and top floor displacement are evaluated as objective functions taking into consideration upper and lower limits of VDs damping coefficients, so that optimal damper placement and properties of shear building can be determined. In this design, VDs-shear building system is tested under three different ground motions being compared to some methods in the literature and uniformly distributed VDs placed at each story. It is shown that, the results of study are both compatible and very successful in reducing the response of structure under the different ground motions.